Optimization of Language Acquisition in Early Childhood Through the Cocomelon YouTube Channel - Desak Made Yoniartini; I Wayan Rasna; I Nengah Suandi; I Putu Mas Dewantara (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2025)
Language acquisition is one of the studies in psycholinguistics. Language acquisition generally occurs in early childhood, namely between the ages of 0 and 5 years. Language acquisition is obtained through many sources, one of which is social media. Social media is currently a human need to interact with other humans. In this study, a qualitative research method was used, by analyzing the videos contained in the Cocomelon channel as a primary source. The results of the study concluded that the Cocomelon YouTube channel is one of the most popular YouTube channels for early childhood, this is evidenced by the number of subscribers and the number of views reaching three billion. By watching the Cocomelon YouTube channel and singing repeatedly, children’s vocabulary will increase and is a form of language acquisition. However, parents must continue to supervise and accompany every child’s growth and development, especially when children surf social media.